The impact of exercising occupational hypocrisy on organizational strategic success: An Empirical study on university of kufa faculty of administration and economic (Journal of Accounting and Financial Studies ( JAFS ), 2014)
This research aims to identify the relationship between occupational hypocrisy and organizational strategic success, It was done by analyzing the correlations and influence between variables,  applied to a random sample of university professors at the University of Kufa faculty of administration and economic. The main tool for data collection is the survey were questionnaires were distributed randomly to the professors , and (43) questionnaires were returned, and test its validity by using (SEM) (Structural Equation Modeling), Hypothesis has been tested by using Statistical Package for Social Sciences (SPSS v. 18), The research found a set of conclusions:(The occupational hypocrisy has a negative influence on the strategic success), and make recommendations.